Engineering General Intelligence, Part 1 A Path to Advanced AGI via Embodied Learning and Cognitive Synergy - Goertzel, Ben.; Pennachin, Cassio; Geisweiller, Nil.; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2014)
The work outlines a novel conceptual and theoretical framework for understanding Artificial General Intelligence and based on this framework outlines a practical roadmap for the development of AGI with capability at the human level and ultimately beyond.
A Brief Overview of Cog Prime -- Build Me Something I Haven't Seen: A Cog Prime Thought Experiment -- What is Human-Like General Intelligence? A Patternist Philosophy of Mind -- Brief Survey of Cognitive Architectures -- A Generic Architecture of Human-Like Cognition -- A Formal Model of Intelligent Agents -- Cognitive Synergy -- General Intelligence in the Everyday Human World -- A Mind-World Correspondence Principle -- Stages of Cognitive Development -- The Engineering and Development of Ethics -- Local, Global and Glocal Knowledge Representation -- Representing Implicit Knowledge via Hypergraphs -- Emergent Networks of Intelligence -- AGI Preschool -- A Preschool-Based Roadmap to Advanced AGI -- Advanced Self-Modification: A Possible Path to Superhuman AGI.
Keywords: Computer science; Neurosciences; Artificial intelligence; Neural networks (Computer science).; Computational intelligence; Complexity, Computational; Computer Science; Artificial Intelligence (incl. Robotics).; Computational Intelligence; Complexity; Neurosciences; Mathematical Models of Cognitive Processes and Neural Networks